Water quality trend of Batang Kayan and its relation to anthropogenic activities - Gwendolyne, Christopher (Faculty Of Resource Science and Technology, 2004)
Biological processes, anthropogenic activities and water resources within a river basin are clearly associated. Thus, water catchment is a good boundary limit to study ecological stress. Over the years, Lundu District has undergone a lot of development especially the agriculture sector. The most dominant land uses in Batang Kayan catchment are oil palm plantations, paddy irrigation schemes, and shifting cultivations. Most of the agricultural projects are concentrated along Batang Kayan as they are depending on Batang Kayan as the source o(water. All the runoffs from the agricultural projects are drained out to Batang Kayan. Thus, a study was carried out to determine the impacts of land use changes on water quality and to evaluate the water quality trend (1997 2003) of Batang Kayan catchment in particular of the Selampit sub-catchment. Field observations, indepth interviews with the villagers, oil plantation managements and government agencies, literature search and water quality sampling and analysis gave indications of water quality issue in this catchment. They are the severe soil erosion, sedimentation and siltation, and leaching of nutrients. The water quality index (WQI) for the river began to deteriorate in 1997 with an index of 79 compared to 88 in 1996. This coincides with the beginning of the massive development of agricultural sector in that district. Human activities have thus caused significant decreased in water quality. Nonetheless, the water quality of Batang Kayan has generally improved due to the stringent enforcement by the government and currently the WQI of the river is 88.